More ideas for science projects - Adams, Richard C. (Richard Crittenden); Gardner, Robert, 1929- (New York : Franklin Watts, 1998)
Presents ideas for science projects in all areas of the discipline, including engineering, and offers suggestions for data collection and analysis using computer software programs.
Includes bibliographical references (p. 147) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Engineering -- Experiments -- Juvenile literature; Science projects -- Juvenile literature; Engineering -- Experiments; Experiments; Science projects; Engineering -- Experiments; Experiments; Science projects; Science -- Experiments